Regulation of Airport Charges in EU Law, and in Poland and Germany: Limits of Airport Managing Bodies’ Autonomy and the Principle of Transparency and Non-Discrimination (Ius Novum, 2025)
This article analyses the regulation of airport charges under European Union law and within the national legal systems of Poland and Germany, with particular focus on the relationship between the autonomy of airport managing bodies and their obligation to observe the principles of transparency and non-discrimination. The authors discuss the legal framework established by Directive 2009/12/EC and examine its implementation in two distinct national contexts. The analysis demonstrates that, although airport managing bodies formally possess the right to determine the level and structure of charges, their discretion is constrained by both EU legislation and national oversight mechanisms.
Keywords: airport charges, non-discrimination, transparency, EU law, EU air transport